Nano cellulose aerogel as well as preparation method and application thereof

The nanocellulose aerogel was prepared by oxidation method and the addition of high fluorine organic matter was solved, which solved the problems of poor thermal insulation performance of building glass and the absorption of water and mold of cellulose aerogels, and achieved a nanocellulose aerogel functional membrane with high hydrophobicity and long life.

CN119798767APending Publication Date: 2025-04-11CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411890107.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The thermal insulation performance of existing buildings is poor, especially in high temperature environments, which makes it difficult to adjust the indoor temperature. Moreover, cellulose aerogels are absorbed and moldy when used in building materials, which affects their service life.

Method used

Nano-sized cellulose molecular group was prepared by oxidation method, and it was prepared as an aerogel by sol-gel method. High fluorine organic matter was added to change the hydrophilicity of cellulose, and nanocellulose aerogel with higher hydrophobic properties were formed.

Benefits of technology

The high hydrophobicity of the nanocellulose aerogel functional membrane is achieved, which extends its service life in humid environments and improves the thermal insulation performance of the building.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to nanocellulose aerogel as well as a preparation method and application thereof. The method comprises the following steps: treating broadleaf wood pulp and extracting cellulose from the pulp; the method comprises the following steps: repeatedly oxidizing cellulose by using an oxidizing agent under the catalysis of an oxidizing aid and sodium hypochlorite, and performing ultrasonic treatment to obtain a nanocrystallized cellulose aqueous solution; and then coating the surface of glass with the nano-cellulose aqueous solution, and spraying diluted hydrochloric acid to gelatinize the glass, so as to obtain the nano-cellulose aerogel. The technical problem to be solved is to prepare a cellulose molecular group with a nano size by an oxidation method, prepare the cellulose molecular group into aerogel by a sol-gel method to obtain the degradable nano cellulose aerogel with light texture, reinforce the aerogel by a high-fluorine organic matter, change the hydrophilicity of cellulose by a plurality of fluorocarbon bonds, and improve the hydrophilicity of cellulose. Therefore, the nanocellulose aerogel functional film has higher hydrophobicity, so that the nanocellulose aerogel functional film can be better used as a thermal insulation layer of a building.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, and in particular relates to a nanocellulose aerogel and a preparation method and application thereof. Background Art

[0002] Global heat emissions and carbon emissions are increasing year by year. The former increases the heat in the atmosphere, while the latter makes it difficult for the heat in the atmosphere to be discharged into the universe, which makes the summer temperature higher and higher. Especially in cities with large emissions, the continuous high temperature is unbearable. How to increase the thermal insulation of building materials and reduce the impact of outdoor temperature on indoor areas in hot summer is one way to solve this problem. Compared with heavy bricks and concrete walls, the thermal insulation performance of thin windows is relatively poor, and it is also the weakest part of the thermal insulation function of the entire building. If the temperature insulation ability of windows can be effectively improved, it will be of great benefit to improving the overall thermal insulation capacity of the building.

[0003] As the main material for windows, glass is thin and light, and not very thick. It is difficult to play an effective role in heat insulation under the current high summer temperatures. Although glass with vacuum insulation interlayer has a heat insulation effect, it will reduce the durability of the glass itself and increase the manufacturing cost. Therefore, using the "lightest solid" aerogel as the heat insulation interlayer to construct a vacuum structure between double-layer glass is an effective way to both play a heat insulation role and reduce the performance requirements of the vacuum interlayer on the glass.

[0004] Nanocellulose-based aerogel is the third generation of aerogel. Compared with traditional cellulose aerogel, it has a series of superior physical and chemical properties such as high specific surface area, high porosity, low thermal conductivity, low cost and biocompatibility. It also has many advantages such as cellulose is non-toxic and pollution-free, easy to biodegrade, sufficient and renewable raw materials, low cost, and waste recycling. The use of nanocellulose to prepare new thermal insulation materials and apply them to special thermal insulation glass can not only solve the shortcomings and problems of existing organic and inorganic thermal insulation materials in my country, but also effectively improve the temperature regulation ability and technological level of new buildings in my country, which is of great significance to the development and innovation of my country's building materials field. However, cellulose is essentially a polysaccharide and a highly hydrophilic substance. When applied to building glass, it will absorb water and rot, reducing its service life. This shortcoming affects the application of cellulose aerogel in building materials. Summary of the invention

[0005] In view of this, the main purpose of the present invention is to provide a nanocellulose aerogel and a preparation method and application thereof. The technical problem to be solved is to prepare nano-sized cellulose molecular groups by an oxidation method, prepare them into aerogels by a sol-gel method, and obtain a lightweight and degradable nanocellulose aerogel, strengthen the aerogel with high-fluorine organic matter, and change the hydrophilicity of cellulose with multiple carbon-fluorine bonds, so that the nanocellulose aerogel functional membrane has higher hydrophobicity.

[0006] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions. According to a method for preparing nanocellulose aerogel proposed in the present invention, it comprises the following steps:

[0007] 1) Soak the hardwood dry pulp in room temperature deionized water for 12 to 24 hours to soften it;

[0008] 2) Add the softened pulp into deionized water, heat it in a water bath and stir it thoroughly for 20 to 24 hours to disperse it into a suspension;

[0009] 3) Add an oxidant and an oxidant aid to the suspension and continue stirring at room temperature for 6 to 8 hours;

[0010] 4) Slowly drop sodium hypochlorite solution into the suspension, react at room temperature for 6 to 8 hours, continue to drop and measure the pH value until the pH value does not change within 10 to 20 minutes; centrifuge, then remove the liquid part and add deionized water of equal weight; repeat the above operation 10 to 20 times; remix the product obtained in the last step to obtain a suspension;

[0011] 5) subjecting the suspension obtained in step 4) to ultrasonic treatment, then adding an oxidant and an oxidizing aid, continuing to stir at room temperature, and continuously dropping a sodium hypochlorite solution until the suspension is stratified, continuing to drop until the state of the opaque layer does not change, centrifuging the stratified suspension, taking the supernatant, diluting the supernatant with an equal weight of deionized water, and filtering to obtain a translucent liquid;

[0012] 6) The opaque liquid obtained in step 5) is evenly spread on the surface of the glass, and the surface is sprayed with dilute hydrochloric acid to gel the liquid on the surface of the glass to form a solid film, thereby obtaining the nanocellulose aerogel.

[0013] Preferably, in the aforementioned method for preparing nanocellulose aerogel, in step 1), the hardwood absolute dry pulp is selected from one of absolute dry poplar pulp, absolute dry maple pulp and absolute dry eucalyptus pulp.

[0014] Preferably, in the aforementioned method for preparing nanocellulose aerogel, in step 2), the mass ratio of the deionized water to the absolute dry hardwood pulp is (10-20):1.

[0015] Preferably, in the aforementioned method for preparing nanocellulose aerogel, in step 2), the water bath heating temperature is 75-85°C.

[0016] Preferably, in the aforementioned method for preparing nanocellulose aerogel, in step 3), the oxidant is 2,2,6,6-tetramethylpiperidine solid powder or propionaldehyde, and the mass ratio of the oxidant to the suspension is 25-30wt%.

[0017] Preferably, in the above-mentioned method for preparing nanocellulose aerogel, in step 3), the oxidizing aid is sodium bromide solid powder or potassium bromide solid powder, and the mass ratio of the oxidizing aid to the suspension is 0.5-1 wt %.

[0018] Preferably, in the aforementioned method for preparing nanocellulose aerogel, in step 3) and step 5), the mass ratio of the oxidant to the oxidizing aid is (10-30):1.

[0019] Preferably, in the above-mentioned method for preparing nanocellulose aerogel, in step 4) and step 5), the centrifugal speed is 8000-10000 rpm and the time is 20-40 min.

[0020] Preferably, in the aforementioned method for preparing nanocellulose aerogel, in step 4) and step 5), the concentration of the sodium hypochlorite solution is 0.5-1 wt%.

[0021] Preferably, in the aforementioned method for preparing nanocellulose aerogel, in step 5), the power of the ultrasound is 30 to 50 kHz and the time is 20 to 40 minutes.

[0022] Preferably, in the aforementioned method for preparing nanocellulose aerogel, in step 5), the oxidant is 2,2,6,6-tetramethylpiperidine solid powder or propionaldehyde, and the mass ratio of the oxidant to the suspension is 5-10wt%.

[0023] Preferably, in the above-mentioned method for preparing nanocellulose aerogel, in step 5), the oxidizing aid is sodium bromide solid powder or potassium bromide solid powder, and the mass ratio of the oxidizing aid to the suspension is 0.5-1 wt %.

[0024] Preferably, in the aforementioned method for preparing nanocellulose aerogel, in step 6), the concentration of the dilute hydrochloric acid is 2-5% (v / v).

[0025] The purpose of the present invention and the technical problems solved therein are also achieved by adopting the following technical solutions: According to a nanocellulose aerogel proposed in the present invention, the nanocellulose aerogel is prepared by the above method.

[0026] The purpose of the present invention and the technical problems solved therein are also achieved by the following technical solutions: A modified fiber-based aerogel proposed in the present invention comprises the above-mentioned nanocellulose aerogel and a high-fluorine organic compound; the high-fluorine organic compound contains a plurality of carbon-fluorine bonds.

[0027] The purpose of the present invention and the technical problem solved by the present invention are also achieved by adopting the following technical solutions. A method for preparing a modified fiber-based aerogel proposed by the present invention comprises the following steps:

[0028] The nanocellulose aerogel spread on the glass surface is placed in an ethanol solution containing 5 to 10 wt% of tridecafluorooctyltriethoxysilane and immersed for 6 to 8 hours to obtain the modified fiber-based aerogel.

[0029] Some embodiments of the present invention also provide a method for preparing a nanocellulose aerogel heat-insulating hydrophobic functional membrane, comprising the following steps:

[0030] The glass with modified fiber-based aerogel is dried at 75-85° C. for 1-2 hours to obtain a nanocellulose aerogel heat-insulating hydrophobic functional membrane containing high-fluorine organic substance tridecafluorooctyltriethoxysilane.

[0031] The purpose of the present invention and the technical problems solved are also achieved by the following technical solutions. According to the nanocellulose aerogel thermal insulation hydrophobic functional membrane proposed by the present invention, the nanocellulose aerogel thermal insulation hydrophobic functional membrane contains 5 to 10 wt% of high-fluorine organic tridecafluorooctyl triethoxysilane; the contact angle of the nanocellulose aerogel thermal insulation hydrophobic functional membrane is greater than 100°, and the membrane thickness is 0.25 to 0.30 mm.

[0032] Preferably, the aforementioned nanocellulose aerogel thermal insulation type hydrophobic functional membrane, wherein the nanocellulose aerogel thermal insulation type hydrophobic functional membrane is prepared by the above method.

[0033] By means of the above technical solution, the nanocellulose aerogel and its preparation method and application proposed in the present invention have at least the following advantages:

[0034] The nanocellulose and its preparation method and application proposed in the present invention prepare nano-sized cellulose molecular groups by oxidation method, prepare them into aerogel by sol-gel method, and obtain a lightweight and degradable nanocellulose aerogel, strengthen the aerogel with high-fluorine organic matter, and change the hydrophilicity of cellulose with multiple carbon-fluorine bonds, so that the nanocellulose aerogel functional film has higher hydrophobicity, which can better serve as the thermal insulation layer of buildings and improve its service life in humid, rainy and snowy environments; actual tests show that the aerogel functional film with the nanocellulose as the main component can be completely degraded in the natural environment in December, and is environmentally friendly compared to the commonly used silicone resin aerogel functional film; further, the contact angle of the nanocellulose aerogel heat-insulating hydrophobic functional film is greater than 100°, compared with 30° of pure cellulose, it has been transformed from a hydrophilic material to a hydrophobic material, which can slow down the erosion of water on its surface and prevent mildew and deterioration.

[0035] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION

[0036] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the following is a detailed description of a nanocellulose aerogel and its preparation method and application according to the present invention, its specific implementation method, structure, characteristics and effects in combination with the preferred embodiments.

[0037] Some embodiments of the present invention provide a method for preparing a nanocellulose aerogel, which comprises the following steps:

[0038] 1) Soak the hardwood dry pulp in deionized water at room temperature for more than 12 hours until it absorbs enough water to soften. Considering the convenience of obtaining, the hardwood dry pulp can be selected from one of poplar dry pulp, maple dry pulp and eucalyptus dry pulp.

[0039] 2) Add the softened pulp to deionized water, heat in a water bath at 75-85°C and stir thoroughly for 20-24 hours to disperse it into a suspension. This step changes the hardwood pulp from a solid state to a suspension water mixture state. The mass ratio of the deionized water to the hardwood absolute dry pulp is (10-20):1; if the mass ratio is less than 10:1, it will result in waste; if the mass ratio is greater than 20:1, it will result in too much raw material and poor reaction effect. If the stirring time is less than 20 hours, the reaction is incomplete, and if it is greater than 24 hours, it will result in waste.

[0040] 3) Add an oxidant to the suspension and an oxidizing aid, continue stirring at room temperature for 6 to 8 hours to obtain a suspension. The mass ratio of the oxidant to the oxidizing aid is (10 to 30):1. When it is lower than 10:1, the oxidation reaction will be more intense and may produce byproducts (such as small molecule sugars); when it is higher than 30:1, the speed cannot be faster, resulting in waste of the oxidant; the oxidant can be TEMPO solid powder (2,2,6,6-tetramethylpiperidine solid powder) or propionaldehyde; the mass ratio of the oxidant to the suspension can be 25 to 30 wt%; if the mass ratio is less than 25 wt%, the oxidation will be incomplete; if the mass ratio is greater than 30 wt%, the oxidant will be wasted. Considering the practicality of pulp, the oxidizing aid can be sodium bromide solid powder or potassium bromide solid powder, which is used to assist the oxidation reaction; the mass ratio of the oxidizing aid to the suspension can be 0.5 to 1 wt%; when it is lower than 0.5 wt%, the oxidation reaction will be incomplete, and when it is higher than 1 wt%, the material will be wasted. This is an oxidation separation process, which removes large impurities (sedimentation) and soluble substances in the pulp while dissociating the high-molecular weight cellulose by oxidation, gradually converting the giant molecular clusters into smaller molecular clusters.

[0041] 4) Slowly add 0.5-1wt% sodium hypochlorite solution to the suspension obtained in step 3), react at room temperature for 6-8h, continue to add and measure the pH value with a pH meter until the pH does not change within 10-20min. This step further decomposes the cellulose molecular clusters into smaller ones. If the concentration of the sodium hypochlorite solution is lower than 0.5wt%, the reaction is too slow; if the concentration of the sodium hypochlorite solution is higher than 1wt%, the reaction is difficult to control;

[0042] 5) The suspension obtained in step 4) is subjected to high-speed centrifugation (8000-10000rpm, 20-40min), and then the liquid portion is removed, and deionized water of the same weight as the removed liquid is added. Repeat the above operation 10-20 times. If it is less than 10 times, the removal is not clean, and if it is more than 20 times, it is a waste of time. The product obtained in the last time is remixed with a stirrer to obtain a suspension. During the centrifugation process, the excess oxidant and oxidation aid are removed, and the cellulose component is purified, and its purity is about 9-11wt%.

[0043] 6) The suspension is subjected to ultrasound (30-50kHz, 20-40min). Then, an oxidant is added, and an oxidant aid is added, stirring is continued at room temperature, and 0.5-1wt% sodium hypochlorite solution is continuously added dropwise until the suspension is stratified. The mass ratio of the oxidant to the oxidant aid is (10-30):1. When it is lower than 10:1, the oxidation reaction will be more intense and may produce by-products (such as small molecule sugars); when it is higher than 30:1, the speed cannot be faster, resulting in waste of oxidant; the oxidant can be TEMPO solid powder (2,2,6,6-tetramethylpiperidine solid powder) or propionaldehyde; the mass ratio of the oxidant to the suspension is 5-10wt%; if the mass ratio is less than 5wt%, incomplete oxidation will result; if the mass ratio is greater than 10wt%, waste of oxidant will result. Considering the practicality of pulp, the oxidation aid can be sodium bromide solid powder or potassium bromide solid powder, which is used to assist the oxidation reaction; the mass ratio of the oxidation aid to the suspension is 0.5-1wt%; when it is lower than 0.5wt%, the oxidation reaction is incomplete, and when it is higher than 1wt%, the material is wasted. This is the secondary oxidation part, the purpose of which is to further dissociate the purified cellulose molecular clusters until they are dispersed into nano-scale molecular clusters. The nano-sizing of cellulose is achieved. If the mass ratio is less than 5wt%, the reaction efficiency is low; if the mass ratio is greater than 10wt%, the reaction is not easy to control. If the amount of the oxidation aid sodium bromide solid powder added is less than 0.5wt%, the reaction efficiency is low; if the amount of the oxidation aid sodium bromide solid powder added is greater than 1wt%, the reaction is not easy to control. The effect of the sodium hypochlorite solution is poor when the concentration is less than 0.5wt%, and it will lead to waste when it is greater than 1wt%.

[0044] 7) Continue to drip until the state of the opaque layer does not change, centrifuge the layered suspension (8000-10000 rpm, 25-35 min), and take the upper clear liquid. This step is to remove the cellulose residue that has not been nanosized and obtain a nanocellulose aqueous solution; the average size of the nanocellulose molecular clusters is below the nanometer size.

[0045] 8) Add an equal amount of deionized water to dilute the supernatant and filter to obtain a translucent liquid.

[0046] 9) The translucent liquid is evenly spread on the surface of the glass, and 2-5% (v / v) dilute hydrochloric acid is sprayed on the surface to make the liquid gel on the glass surface to form a solid film. This step is the process of sol-gel formation of aerogel. Specifically, the nanocellulose aqueous solution is covered on the surface of the glass and allowed to level naturally; 2-5% (v / v) dilute hydrochloric acid is sprayed on the surface in a mist form with a sprayer to make the nanocellulose aqueous solution undergo a sol-gel reaction on the glass surface, forming a thin porous colloidal layer solid on the glass surface, and thus obtaining the nanocellulose aerogel.

[0047] Some embodiments of the present invention further provide a nanocellulose aerogel, wherein the nanocellulose aerogel is prepared by the above method.

[0048] Some embodiments of the present invention also provide a modified fiber-based aerogel, which comprises the above-mentioned nanocellulose aerogel and a high-fluorine organic matter, wherein the nanocellulose aerogel is composited with the high-fluorine organic matter to convert its hydrophilicity into hydrophobicity; the high-fluorine organic matter comprises a plurality of carbon-fluorine bonds, and since tridecafluorooctyltriethoxysilane has a strong permeability, a large number of carbon-fluorine bonds can be introduced into the structure of the nanocellulose aerogel using ethanol as a solvent; the carbon-fluorine bonds have a strong hydrophobicity.

[0049] Some embodiments of the present invention also provide a method for preparing a modified fiber-based aerogel, comprising the following steps:

[0050] The nanocellulose aerogel spread on the surface of the glass is placed in an ethanol solution of 5-10wt% tridecafluorooctyl triethoxysilane and soaked for 6-8h to obtain the modified fiber-based aerogel. This step is a process in which high-fluorine organic matter penetrates and mixes into the aerogel. Specifically, the porous colloidal layer solid is immersed in an ethanol solution of tridecafluorooctyl triethoxysilane together with the glass, so that the tridecafluorooctyl triethoxysilane fully penetrates into the interior of the colloidal layer to obtain glass with modified fiber-based aerogel, that is, the modified fiber-based aerogel. If the concentration of tridecafluorooctyl triethoxysilane is less than 5wt%, the effect is poor; if the concentration of tridecafluorooctyl triethoxysilane is greater than 10wt%, it leads to waste of materials.

[0051] Some embodiments of the present invention also provide a method for preparing a nanocellulose aerogel heat-insulating hydrophobic functional membrane, comprising the following steps:

[0052] The glass with the modified fiber-based aerogel is dried at 75-85°C for 1-2 hours to remove the azeotrope of water and ethanol, thereby obtaining glass with an aerogel functional film. This step is a process for removing the solvent to obtain a functional film. If the drying temperature is lower than 75°C, the drying effect is poor; if the drying temperature is higher than 85°C, the modified fiber-based aerogel on the glass may be damaged.

[0053] Specifically, the colloidal layer together with the glass is dried at 75-85°C for 1-2 hours to remove water and ethanol residues, and then left overnight or for half a day to obtain a nanocellulose aerogel insulating hydrophobic functional membrane containing high-fluorine organic substance tridecafluorooctyltriethoxysilane.

[0054] Some embodiments of the present invention also provide a nanocellulose aerogel thermal insulation hydrophobic functional membrane, wherein the nanocellulose aerogel thermal insulation hydrophobic functional membrane contains 5 to 10 wt % of a high-fluorine organic substance, tridecafluorooctyltriethoxysilane; the contact angle of the nanocellulose aerogel thermal insulation hydrophobic functional membrane is greater than 100°, and the membrane thickness is 0.25 to 0.30 mm; the nanocellulose aerogel thermal insulation hydrophobic functional membrane is prepared by the above method.

[0055] The key points of the above technical solutions are mainly in the following aspects:

[0056] On the one hand, the preparation of cellulose aerogel is achieved through the process of nano-cellulose. Ordinary cellulose molecular clusters are large and tend to self-aggregate in solution, and it is difficult to prepare aerogels with uniform texture by the sol-gel method. The technical solution of the present invention uses a secondary oxidation method to dissociate the large molecular clusters of ordinary cellulose into small molecular clusters at the nanoscale, so that it has better dispersibility in aqueous solution and is easier to form aerogels with uniform texture, which simplifies the conditions for forming aerogels and effectively improves the yield and uniformity of aerogels.

[0057] On the other hand, high-fluorine organic matter is used to infiltrate the aerogel structure. Since tridecafluorooctyl triethoxysilane has strong permeability and is soluble in ethanol, its ethanol solution is used to soak the aerogel to allow as much high-fluorine organic matter as possible to penetrate into the aerogel. The originally hydrophilic nanocellulose aerogel is converted into a hydrophobic one, thereby improving its resistance to the humid environment caused by water vapor and rain and snow in nature and extending its service life. In addition, the ethanol and water in this process can be mixed and removed, and the removal process will not cause serious deformation of the aerogel functional membrane and affect its performance.

[0058] In the above technical scheme, the wood pulp and deionized water are used as the reaction raw materials; before adding the oxidant to the reaction, the reaction raw materials are preferably subjected to sufficient anaerobic dispersion treatment. Specifically, the reactants are added to the reactor, stirred for more than 12 hours in a nitrogen atmosphere with a purity of 99.99% at room temperature, and then the oxidant is added thereto for subsequent reaction.

[0059] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0060] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.

[0061] The testing methods of the film thickness and water contact angle of the following embodiments and comparative examples are as follows: the film thickness is tested by a film thickness tester; the water contact angle is tested by a contact angle meter.

[0062] Example 1

[0063] a. Soak 50g of dry poplar pulp in deionized water (1L) at room temperature for 24h to soften it. Take out the softened pulp and put it into a beaker, add 500g of deionized water, heat it in a water bath at 80℃ and stir it at 200rpm / min for 24h to form a suspension. Add 15g of TEMPO solid powder to the suspension, and add 0.5g of sodium bromide solid powder, and continue stirring at room temperature for 6h. Slowly add 1wt% sodium hypochlorite solution to the suspension, continue to react at room temperature for 6h, and continue to add until the pH value does not change within 20min.

[0064] b Centrifuge (8000rpm, 30min) the suspension after the above reaction, remove the liquid part and add deionized water of the same weight as the removed liquid. Repeat 10 times. The product obtained in the last time was remixed with a stirrer (200rpm, 2h) until it was dispersed to obtain a suspension. Then the obtained suspension was ultrasonicated at 40Hz for 30min. Then 5.5g of TEMPO solid powder and 0.5g of sodium bromide solid powder were added, and stirring at room temperature was continued (200rpm, 6h), and 1wt% sodium hypochlorite solution was continuously added dropwise until the suspension was layered. Continue to add dropwise until the state of the opaque layer does not change, centrifuge the layered suspension (8000rpm, 30min), and take the supernatant. The supernatant was diluted with deionized water of the same weight as the supernatant, and filtered (to remove residual impurities) to obtain a translucent liquid, that is, an aqueous solution of nanocellulose.

[0065] c. The translucent liquid is evenly covered on the surface of the glass, and leveled naturally. The surface is sprayed with 2% (v / v) dilute hydrochloric acid mist to make the liquid gel on the glass surface and form a solid film. When the solid does not change significantly, it is placed together with the glass in an ethanol solution of 10wt% tridecafluorooctyl triethoxysilane and immersed for 6 hours.

[0066] d. Dry the glass with the film at 80°C for 1 h to remove the azeotrope of water and ethanol, thereby obtaining glass with an aerogel functional film.

[0067] According to the test, the glass with the aerogel functional film of this embodiment has a film thickness of 0.3 mm and a water contact angle of 105°.

[0068] Example 2

[0069] a Soak 20g of dry poplar pulp in deionized water (1L) at room temperature for 24h to soften it. Take out the softened pulp and put it into a beaker, add 200g of deionized water, heat it in a water bath at 80℃ and stir it at 200rpm / min for 24h to form a suspension. Add 6g of TEMPO solid powder to the suspension, and add 0.2g of sodium bromide solid powder, and continue stirring at room temperature for 8h. Slowly add 1wt% sodium hypochlorite solution to the suspension, continue to react at room temperature for 8h, and continue to add until the pH value does not change within 20min.

[0070] b Centrifuge (8000rpm, 30min) the suspension after the above reaction (200rpm, 6h), remove the liquid part and add deionized water of equal weight to the removed liquid. Repeat 10 times. The product obtained last time was remixed with a stirrer (200rpm, 2h) until the suspension was dispersed. Then the obtained suspension was ultrasonicated at 40Hz for 30min. Then 2.2g of TEMPO solid powder and 0.2g of sodium bromide solid powder were added, and stirring at room temperature was continued (200rpm, 6h), and 1wt% sodium hypochlorite solution was continuously added until the suspension was layered. Continue to add until the state of the opaque layer does not change, centrifuge the layered suspension (8000rpm, 30min), and take the supernatant. The supernatant was diluted with deionized water of equal weight to the supernatant, and filtered to obtain a translucent liquid, that is, an aqueous solution of nanocellulose was obtained.

[0071] c. The translucent liquid is evenly covered on the surface of the glass, and leveled naturally. The surface is sprayed with 2% (v / v) dilute hydrochloric acid mist to make the liquid gel on the glass surface and form a solid film. When the solid does not change significantly, it is placed together with the glass in an ethanol solution of 10wt% tridecafluorooctyl triethoxysilane and immersed for 6 hours.

[0072] d. Dry the glass with the film at 80°C for 1 h to remove the azeotrope of water and ethanol, thereby obtaining glass with an aerogel functional film.

[0073] According to the test, the glass with the aerogel functional film of this embodiment has a film thickness of 0.25 mm and a water contact angle of 103°.

[0074] Example 3

[0075] a Soak 30g of dry poplar pulp in deionized water (1L) at room temperature for 24h to soften it. Take out the softened pulp and put it into a beaker, add 300g of deionized water, heat it in a water bath at 80℃ and stir it at 200rpm / min for 24h to form a suspension. Add 9g of TEMPO solid powder to the suspension, and add 0.3g of sodium bromide solid powder, and continue stirring at room temperature for 8h. Slowly add 1wt% sodium hypochlorite solution to the suspension, continue to react at room temperature for 8h, and continue to add until the pH value does not change within 10min.

[0076] b Centrifuge (8000rpm, 30min) the suspension after the above (200rpm, 6h) reaction, remove the liquid part and add deionized water of equal weight to the removed liquid. Repeat 10 times. The product obtained last time was remixed with a stirrer (200rpm, 2h) until the suspension was dispersed. Then the obtained suspension was ultrasonicated at 40Hz for 30min. Then 3.3g of TEMPO solid powder and 0.3g of sodium bromide solid powder were added, and stirring at room temperature was continued (200rpm, 6h), and 1wt% sodium hypochlorite solution was continuously added until the suspension was layered. Continue to add until the state of the opaque layer does not change, centrifuge the layered suspension (8000rpm, 30min), and take the supernatant. The supernatant was diluted with deionized water of equal weight to the supernatant, and filtered to obtain a translucent liquid, that is, an aqueous solution of nanocellulose was obtained.

[0077] c. The translucent liquid is evenly covered on the surface of the glass, and leveled naturally. The surface is sprayed with 2% (v / v) dilute hydrochloric acid mist to make the liquid gel on the glass surface and form a solid film. When the solid does not change significantly, it is placed together with the glass in an ethanol solution of 10wt% tridecafluorooctyl triethoxysilane and immersed for 6 hours.

[0078] d. Dry the glass with the film at 80°C for 1 h to remove the azeotrope of water and ethanol, thereby obtaining glass with an aerogel functional film.

[0079] According to the test, the glass with the aerogel functional film of this embodiment has a film thickness of 0.30 mm and a water contact angle of 107°.

[0080] Example 4

[0081] The difference between this embodiment and embodiment 3 is that in step a of this embodiment, the amount of TEMPO solid powder added is 9 g, and the amount of sodium bromide solid powder added is 0.9 g; the remaining steps and parameters are the same as those in embodiment 3.

[0082] According to the test, the glass with the aerogel functional film of this embodiment has a film thickness of 0.28 mm and a water contact angle of 110°.

[0083] Example 5

[0084] The difference between this embodiment and embodiment 3 is that in step a of this embodiment, the amount of TEMPO solid powder added is 9 g, and the amount of sodium bromide solid powder added is 0.45 g; the remaining steps and parameters are the same as those in embodiment 3.

[0085] According to the test, the glass with the aerogel functional film of this embodiment has a film thickness of 0.29 mm and a water contact angle of 108°.

[0086] Example 6

[0087] The difference between this embodiment and embodiment 3 is that in step b of this embodiment, the amount of TEMPO solid powder added is 3.3 g, and the amount of sodium bromide solid powder added is 0.11 g; the remaining steps and parameters are the same as those in embodiment 3.

[0088] According to the test, the glass with the aerogel functional film of this embodiment has a film thickness of 0.31 mm and a water contact angle of 111°.

[0089] Comparative Example 1

[0090] The difference between this comparative example and Example 3 is that in step a of this comparative example, the amount of TEMPO solid powder added is 9 g, and the amount of sodium bromide solid powder added is 1.0 g; the remaining steps and parameters are the same as those in Example 3.

[0091] After testing, the glass with the aerogel functional film in this comparative example has a film thickness of 0.39 mm and a water contact angle of 95°.

[0092] Comparative Example 2

[0093] The difference between this comparative example and Example 3 is that in step a of this comparative example, the amount of TEMPO solid powder added is 9 g, and the amount of sodium bromide solid powder added is 0.225 g; the remaining steps and parameters are the same as those in Example 3.

[0094] After testing, the glass with the aerogel functional film in this comparative example has a film thickness of 0.31 mm and a water contact angle of 108°.

[0095] Comparative Example 3

[0096] The difference between this comparative example and Example 3 is that in step b of this comparative example, the amount of TEMPO solid powder added is 3.3 g, and the amount of sodium bromide solid powder added is 0.4 g; the remaining steps and parameters are the same as those in Example 3.

[0097] After testing, the glass with the aerogel functional film in this comparative example has a film thickness of 0.37 mm and a water contact angle of 97°.

[0098] Comparative Example 3

[0099] The difference between this comparative example and Example 3 is that in step b of this comparative example, the amount of TEMPO solid powder added is 3.3 g, and the amount of sodium bromide solid powder added is 0.1 g; the remaining steps and parameters are the same as those in Example 3.

[0100] After testing, the glass with the aerogel functional film in this comparative example has a film thickness of 0.28 mm and a water contact angle of 105°.

[0101] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.

[0102] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing nanocellulose aerogel, characterized in that: The following steps are involved: 1) Soak the hardwood dry pulp in room temperature deionized water for 12 to 24 hours to soften it; 2) Add the softened pulp into deionized water, heat it in a water bath and stir it thoroughly for 20 to 24 hours to disperse it into a suspension; 3) Add an oxidant and an oxidant aid to the suspension and continue stirring at room temperature for 6 to 8 hours; 4) Slowly drop sodium hypochlorite solution into the suspension, react at room temperature for 6 to 8 hours, continue to drop and measure the pH value until the pH value does not change within 10 to 20 minutes; centrifuge, then remove the liquid part and add deionized water of equal weight; repeat the above operation 10 to 20 times; remix the product obtained in the last step to obtain a suspension; 5) subjecting the suspension obtained in step 4) to ultrasonic treatment, then adding an oxidant and an oxidizing aid, continuing to stir at room temperature, and continuously dropping a sodium hypochlorite solution until the suspension is stratified, continuing to drop until the state of the opaque layer does not change, centrifuging the stratified suspension, taking the supernatant, diluting the supernatant with an equal weight of deionized water, and filtering to obtain a translucent liquid; 6) The opaque liquid obtained in step 5) is evenly spread on the surface of the glass, and the surface is sprayed with dilute hydrochloric acid to gel the liquid on the surface of the glass to form a solid film, thereby obtaining the nanocellulose aerogel.

2. The preparation method according to claim 1, characterized in that: In step 1), the hardwood dry pulp is selected from one of poplar dry pulp, maple dry pulp and eucalyptus dry pulp; in step 2), the mass ratio of deionized water to hardwood dry pulp is (10-20):1; the water bath heating temperature is 75-85°C.

3. The preparation method according to claim 1, characterized in that: In step 3), the oxidant is 2,2,6,6-tetramethylpiperidine solid powder or propionaldehyde, and the mass ratio of the oxidant to the suspension is 25-30wt%; the oxidizing aid is sodium bromide solid powder or potassium bromide solid powder, and the mass ratio of the oxidant to the suspension is 0.5-1wt%; in step 3) and step 5), the mass ratio of the oxidant to the oxidizing aid is (10-30):

1.

4. The preparation method according to claim 1, characterized in that: In step 4) and step 5), the centrifugal speed is 8000-10000 rpm, the time is 20-40 min; the concentration of the sodium hypochlorite solution is 0.5-1 wt%.

5. The preparation method according to claim 1, characterized in that: In step 5), the power of the ultrasound is 30 to 50 kHz, and the time is 20 to 40 min; the oxidant is 2,2,6,6-tetramethylpiperidine solid powder or propionaldehyde, and the mass ratio of the oxidant to the suspension is 5 to 10 wt%; the oxidizing aid is sodium bromide solid powder or potassium bromide solid powder, and the mass ratio of the oxidant to the suspension is 0.5 to 1 wt%; in step 6), the concentration of the dilute hydrochloric acid is 2 to 5% (v / v).

6. A nanocellulose aerogel, characterized in that: The nanocellulose aerogel is prepared by the method according to any one of claims 1 to 5.

7. A modified fiber-based aerogel, characterized in that: It comprises the nanocellulose aerogel as claimed in claim 6 and a high-fluorine organic compound; the high-fluorine organic compound contains a plurality of carbon-fluorine bonds.

8. A method for preparing the modified fiber-based aerogel according to claim 7, characterized in that: The following steps are involved: The nanocellulose aerogel spread on the glass surface is placed in an ethanol solution containing 5 to 10 wt% of tridecafluorooctyltriethoxysilane and immersed for 6 to 8 hours to obtain the modified fiber-based aerogel.

9. A method for preparing a nanocellulose aerogel heat-insulating hydrophobic functional membrane, characterized in that: The following steps are involved: The glass with modified fiber-based aerogel is dried at 75-85° C. for 1-2 hours to obtain a nanocellulose aerogel heat-insulating hydrophobic functional membrane containing high-fluorine organic substance tridecafluorooctyltriethoxysilane.

10. A nanocellulose aerogel heat-insulating hydrophobic functional membrane, characterized in that: The nanocellulose aerogel thermal insulation hydrophobic functional membrane contains 5 to 10 wt % of high-fluorine organic substance tridecafluorooctyltriethoxysilane; the contact angle of the nanocellulose aerogel thermal insulation hydrophobic functional membrane is greater than 100°, and the membrane thickness is 0.25 to 0.30 mm; the nanocellulose aerogel thermal insulation hydrophobic functional membrane is prepared by the method described in claim 9.